Studi Komperasi Model Pembelajaran Talking Stick dan Snowball Throwing Terhadap Hasil Belajar Berdasarkan Taksonomi Bloom - Marlindoaman Saragih; Risjunardi Damanik (Journal of Natural Sciences, 2022)
This study aims to determine the difference in learning outcomes and the magnitude of the differences in student learning outcomes using the Talking Stick and Snowball Throwing learning models on the excretion system material in class VIII SMP Swasta Bina Guna Tanah Jawa. This research is a type of quasi-experimental research that is given different treatment in each class. The research sample was taken using a saturated sampling technique (census) which consisted of 2 classes, namely class VIII-1 as experiment 1 with 32 students using the Talking Stick learning model, while class VIII-2 into experiment 2 with 32 students using the Snowball Throwing learning model, total of sample is 64 students. Data analysis was carried out by finding the mean (X ), standard deviation (S) and hypothesis testing (t test) at a significance level of = 0.05. From the results of the study, the average value of post-test experiment 1 was 86.56 and experimental 2 was 85.93 with a difference in learning outcomes of 0.63. From the results of hypothesis testing (t test) obtained tcount (1.708) t table (1.669) at the significance level = 0.05 and degrees of freedom (dk) = 32, then Ho is rejected and Ha is accepted, meaning that there are differences in student learning outcomes using the model Talking Stick and Snowball Throwing lessons.